Islamic Religious Education Teachers' Efforts in Implementing Multicultural Education to Grade Ix Students at State Junior High School 11 Baubau - Inang, Inang; Madi, Madi; Basri, Basri; Rahim, Abdul (Jurnal Ilmu Pendidikan dan Humaniora, 2025)
This study aims to analyze the efforts of Islamic Religious Education (PAI) teachers in implementing multicultural education at State Junior High School 11 Baubau and its impact on students. The methods used include the integration of multicultural values ​​in learning, heterogeneous group discussions, case studies, and extracurricular activities. The results of the study indicate that this approach is effective in increasing students' awareness of tolerance, changing social interaction patterns, and reducing conflicts and social stereotypes. However, there are challenges such as differences in student understanding, limited resources, and the influence of the family environment. Therefore, a strategy is needed to strengthen the curriculum, teacher training, increase diversity-based activities, and the involvement of parents and the community to support the sustainability of multicultural education in schools.